PENGARUH METODE PEMBELAJARAN AKTIF TIPE PLANTET QUESTION TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI SEMESTER GENAP SMK WASKITA BEKRI LAMPUNG TENGAHTAHUN PELAJARAN 2014-2015 - Fitria, Nur (LPPM STKIP PGRI Bandar Lampung, 2015)
One contributing factor in the success of the learning process is the use of teaching methods. One method that already exists but has not been used is the type of active learning methods plantet question. The problem in this research is the effect of the application of active learning methods plantet type of question on the results of the economic study from class XI, student of SMK Waskita Central Lampung Bekri school year 2014/2015.The author in this study using an experimental method, as well as data analysis using statistical formulas. The population in this study are all students of class XI SMK Central Lampung Bekri Waskita consisting of 2 classes the number of students 99 students, whereas samples taken two classes of grade XI AP 1 as an experimental class and class XI AP 2 as the control class by using the cluster technique random sampling.From the results of statistical hypothesis testing using t-test formula for normal data and homogeneous, the value thit = 6,08. From the t distribution table at significant level of 5% is known tdaf = t (1-1 / 2Î±) = 2.00 means thit> tdaf. It is hereby concluded that